Ship passing through straits - Paulauskas, Vytautas (Transport, 2010)
All ports and a number of waterways have straits to optimize investments in developing such systems reaching the maximum results with minimum expenditures. New high accuracy port navigational systems have a possibility of high precision ship positioning and any time should guarantee shipping safety in port waters which makes a good basis for the optimization of port development. A new type of ships with good steering equipment and ship steering knowledge and methods in combination with very high accuracy port navigational systems such as E‐Sea Fix and horizontal/vertical port channel bottom scanning possibilities guaranteeing real port water bottom conditions could stimulate dramatically increasing ship sizes at the port entrance in case of guaranteed shipping safety. With reference to straits, a theoretical study and experimental results received by simulators and real ships under much the same conditions have delivered a new knowledge of the limit of big ship sailing in straits and the possibilities of increasing ship size under similar sailing conditions. The Klaipeda strait is taken as the case study for practical testing. The paper presents the results, conclusions and recommendations of a theoretical and practical study for the ships of an increased size at strait ports.First published online: 10 Feb 2011